5. THE CURRENT SITUATION OF THE USE OF ANTIBIOTICS ON SURGICAL PA-TIENTS AT THAI BINH GENERAL HOSPITAL IN 2020 (Vietnam Journal of Community Medicine, 2023)
Background: In recent decades, antibiotic resistance of pathogenic bacteria has become a topconcern in the health sector of many countries, including Vietnam.Objectives: Describe the current situation of antibiotic use on surgical patients at Thai Binh GeneralHospital in 2020.Methods: Cross-sectional survey, quantitative research.Results: 100% of patients use antibiotics after surgery. None of the patients were using a prophylacticantibiotic regimen. The antibiotic group most used is beta-lactam, of which Cephalosporin generation3 accounts for 87.4% and 46,9% was 5-nitro-imidazoles.
Keywords: Use antibiotics, Surgical patients, Thai Binh general Hospital.